Prenatal Diagnosis and Fetomaternal Outcomes of Two Cases with Placental Chorioangioma - Burcu Artunc Ulkumen; Halil Gursoy Pala; Nalan Nese; Yesim Baytur (Case Reports in Obstetrics and Gynecology)
Placental chorioangiomas greater than 4 cm in diameter are rare placental tumors. They have adverse fetomaternal outcomes. We present our experience with two cases having a giant angioma and review the relevant literature.